A report on the practice in industry training in fish preservation. - Nazario, Gloria D. (College of Fisheries, University of the Philippines, 1965)
This thesis is made solely to serve as an introduction or guide to students who endeavour to further their studies in the effect of bacteria upon fish spoilage. It is concerned primarily with the action of antibiotics in retarding the physical and chemical decomposition of fish acted upon bacteria causing spoilage. An elementary introduction to the principles of identification of bacteria, clony counting, inoculation of bacteria and staining; is included to establish a working basis for the study of bacteria present in fish. It is imperative that student acquainted himself with bacteria that is always found to cause fish spoilage. Although this thesis is intended primarily to help the undergraduate students, it is believe that the information given will also be of great value to researchers, fish inspectors, fish technologists, and those engaged in the preservation of fish in commercial scale. The references listed at the end of the thesis are for the benefit of the students; they have been chosen to assist them in becoming more familiar with the subject. It is hoped that this work would enlighten and serve as a nucleus for further research on the control of bacterial spoilage in fish and fishery products.